TINDAK TUTUR EKSPRESIF DALAM FILM MIRACLE IN CELL NO. 7 VERSI INDONESIA KARYA HANUNG BRAMANTYO - Jesika, Jesika; Syam, Christanto; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research focuses on analyzing the forms of expressive speech acts in the movie titled " Miracle In Cell no.7" by director Hanung Bramantyo to find out and understand what forms of expressive speech acts are spoken by the characters in the film. This research was conducted based on the researcher's interest in expressive speech acts within several scenes in the film. The method used in this research is descriptive qualitative. The data samples are collected with several techniques that consists of documentary studies & observation techniques. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The research results show that in the film Miracle In Cell No. 7 there are 5 forms of speech acts, including thanking, apologizing, congratulating, praising and criticizing. The speech act of thanking functions to express gratitude for a reciprocation, the speech act of apologizing functions to express regret for a mistake, the speech act of congratulations functions to appreciate someone's achievements, the speech act of praising functions as someone's admiration, and the speech act of criticizing serves to express disagreement. The research implementation plan is in the form of a teaching module on drama texts in Senior High School (SMA) class XI, even semester of the independent curriculum.